Vozes dos professores de matemática e física: os impactos do “novo” ensino médio em uma escola estadual de Itacoatiara - Rodrigues, Raimunda Figueiredo (Brasil, 2024)
The text describes a research that was carried out in a state school in the municipality of Itacoatiara, in the State of Amazonas. The research aimed to listen to Mathematics and Physics teachers and analyze the impacts of the new high school model, which adopted the National Common Curricular Base (BNCC) from 2022 onwards. Mathematics and Physics addressed the themes of the BNCC, the New Secondary School and the Training Itineraries. The educational policies adopted in recent years for secondary education were followed, including Provisional Measure No. 746/2016 and Law No. 13,415/2017. The implementation of the Amazonas Curricular Reference (RCA) in the new high school was examined, as well as the challenges faced by teachers with this new reform. With this, the research will be based on a bibliographical analysis, field research adhered to a qualitative approach, interviews with teachers from the state public network of Amazonas. Critically reflecting on educational policies and the context of secondary education, in addition to identifying the conditions and difficulties faced by teachers in the implementation of the New Secondary Education and the impact of the Reform on school life.